Employee Attendance Optimization Using QR Code Model with Reed Solomon Error Correction for Data Security and Accuracy - Martono, Aris; Padeli, Padeli; Suhaepi, Muhamad Iip (Journal Sensi: Strategic of Education in Information System, 2025)
This research aims to determine the process of creating a quick response code (QR code) model with Reed Solomon error correction for employee attendance at the Company. Fingerprint attendance systems, even though they are more sophisticated, still have disadvantages, such as difficulties in use in unhygienic environments, as well as high costs for installing the device. Apart from that, traditional attendance is also less flexible in managing employees who work in the field or employees who do not work in the main office. Companies that have many branches or employees who work outside the main office often have difficulty monitoring absenteeism effectively and accurately. The mechanism of this QR code model is carried out through several steps, namely: coding QR codes based on employee ID numbers, grouping encoder data every 8 bits, converting encoder data to binary format, error correction using the Reed Solomon algorithm, creating error correction codes (EC). ) in polynomial form, calculating error correction data based on the correspondence and index of integer numbers in the Galois Field (GF), calculating the function f′(x) through an iterative division process until completion, determining the remainder of the division in the form of R(x), as well as merging encoder data with error correction code as result end. With this mechanism, the QR code-based attendance system is able to maintain data security and accuracy while minimizing the occurrence of anomalies during the work attendance process.